Gambaran Prevalensi Karies Pada Anak Usia 3-5 Tahun Yang Mengkonsumsi ASI dan Susu Botol :Kajian Pada PAUD Sapta Kemuning, Depok Jawa Barat (Laporan Penelitian) - Rara Alvianur; Jeddy Jeddy (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Oral health problems can affect children's general development, general body health and also have a negative impact on children's quality of life. The high rate of early caries in children with the insidence of active dental caries in Indonesia from 53.2% in 2013 increased to 57.6% in 2018 according to the 2018 Basic Health Research data. The high rate of early caries in children begins with breast milk consumption (0 – 6 months) and increases use of bottled milk during the first 6 months after birth. The habit of drinking milk before bed by using a bottle that is too long, also the habit of sucking candy and sweet foods can cause children to get caries. Objective: To describe the early caries prevalence in children aged 3-5 years who consume breast milk and bottled milk in Early Childhood Education Sapta Kemuning, Depok, West Java.  Methods: This study was a descriptive observational study with a cross sectional approach to describe the prevalence of caries in 56 children aged 3-5 years who consumed breast milk and bottled milk according to the inclusion criteria. The child is examined def-t by the lecture, the parents are given a questionnaire containing 3 questions which include the type of intake given to the child, the frequency of administration, and the position of the child when given the intake that has been tested for validity and reliability. Results: Obtained a mean of def-t 6.4 (high). The results showed that 40 children consumed breast milk and 10 children who consumed bottled milk were exposed to caries with an average def-t value of 6.2 (high) and 7.0 (very high). Conclusion: The results showed that the largest caries prevalence in PAUD Sapta Kemuning students was caused by breast milk consumption which was 95% followed by bottle milk consumption of 83%.